Cosmological perturbations in brane-world theories: Formalism - Van De Bruck, G; Dorca, M; Brandenberger, R; Lukas, A (2000)
We develop a gauge-invariant formalism to describe metric perturbations in five-dimensional brane-world theories. In particular, this formalism applies to models originating from heterotic M theory. We introduce a generalized longitudinal gauge for scalar perturbations. In this gauge, we derive the five-dimensional evolution equations for scalar perturbations as well as the most general structure of the scalar brane stress-energy tensor. As an application, we discuss some aspects of the evolution of fluctuations on the brane. Moreover, we show how the five-dimensional formalism can be matched to the known four-dimensional one in the limit where an effective four-dimensional description is appropriate. ©2000 The American Physical Society.